Modeling And Identification Of An Underwater Glider. - Ali Hussain, Nur Afande; Arshad, Mohd Rizal; Mohd Mokhtar, Rosmiwati (2010)
Underwater gliders are type of autonomous underwater vehicle that glide by controlling their buoyancy and attitude using internal actuators.